The effect of Indigofera Leaf Flour (Indigofera Sp.) with Cocktail Enzymes Treatment in Male Ducks Feed on Growth Performance - Djunaidi, Irfan H.; Azizah, Siti; Rachmawati, Achadiah; Prayogi, Heni Setyo (Technium BioChemMed, 2021)
This experimental study aims to evaluate the use of Indigofera leaves that have undergone cocktail enzyme treatment in male Mojosari duck feed. The research treatment was using Indigofera leaves due to enzyme cocktail treatment on male Mojosari duck feed with four levels: 0, 5, 10 and 15% of total feed, with six replications (@ five ducks) using 120 ducks in a completely randomized design. The variables measured and observed in this study were the production performance of male ducks, which included feed consumption, body weight growth, feed conversion. The research results were processed by analysis of variance (ANCOVA) because the coefficient of variation in initial body weight was 17.7%. The results showed that the addition of Indigofera leaf meal to the feed of male Mojosari ducks tended to reduce feed consumption (P<0.01) and body weight gain (P<0.05) but did not increase the FCR value (P>0.05). Indigofera flour needs to be processed first with a cocktail enzyme treatment to improve its nutritional quality so that it can be used as feed for ducks in larger quantities. Male Mojosari ducks that are kept need to be harvested at more than seven weeks to get a higher harvest weight.